محي الدين القليبي ومساهمته في الحركة الوطنية التونسية - دويم, عبد الباري; تامة, رشيد (جامعة الوادي - University of Eloued, 2023)
من خلال دراستنا لشخصية محي الدين القليبي تبين لنا تأثير الأوضاع السياسية والإقتصاديةوالإجتماعيةلتونس خلال فترة الحماية الفرنسية في تكوين شخصيته وإنعكاسها علىأفكاره ، والتي ساهمت في بروزه كأحد زعماء الحركة الوطنية التونسية ، وكانت له مواقف ضد سلطات الحماية بعد إنضمامهالى المصلحين والشباب المثقف،وإهتم بالصحافة التي كانت الباب الذي إستطاع من خلاله فهم السياسية والكفاح الوطني، وقد أعجب به الشيخ عبد العزيز الثعالبي مما جعله يعرض عليه الدخول للحزب الحر الدستوري الذي تولى قيادته بعد رحيله إلى المشرق 1923، وكتب في العديد من الصحف الحزبية مثل: الإتحاد، مرشد الأمة...،و منذ انضمامه للحزب الحر الدستوري التونسي سعى لتحقيق استقلال تونس خاصة بعد توليه قيادة الحزب، وقد كان من الرافضينلإنضمام جماعة العمل التونسي للجنة التنفيذية للحزب الدستوريفي مؤتمر نهج الجبل ، ونتيجة الخلافات التي ترتب عنهاإنشقاق الحزب وظهور الحزب الدستوري الجديد في مؤتمر قصر الهلال في مارس 1934 ، وعند توليه رئاسة الحزب الدستوري القديم بعد وفاة الثعالبي 1944 عمل على ربط القضية التونسية بقضايا المشرق والمغرب، وذلك من خلال عمله في لجنة الدفاع عن افريقيا الشمالية ولجنة تحرير المغرب العربي، بالإضافة الى إهتمامه بالقضايا الإسلامية وفي مقدمتها القضية الفلسطنية التي نضال من أجلها، و بقي يناضل من أجل القضية التونسية والفلسطنية بعد استقراره في دمشق الى أن وافته المنية.Through our study of the personality of MohieddineKlibi, it was apparent to us the impact of the political, economic, and social situation of Tunisia during the French protectorate period in the formation of his personality and its impact on his ideas, which helped him to be one of the leaders of the Tunisian national movement. He had a stance against the protective authorities after joining the reformers and educated youth. He was interested in journalism, which was the door he understood politics and national resistance through. Sheikh AbdelazizTha’albi was impressed by him, which he offered him to enter the constitutional liberal party, Since he joined the constitutional liberal party, he was aiming to grant Tunisia its own independence. After taking over the party’s leadership, he was one of theopposes to the Tunisian workers’ party to join the executivecommittee of the constitutional party at the Nahj Al-Jabal conference, as a result of the disputes that led to the party’s split and the appearance of the new constitutional party at the Qasar Al-Hilal conference in March 1934. When he took over the presidency at the old constitutional party after the death of Tha’albi in 1944, he worked in linking the Tunisian cause with the Levant and Moroccan cause, through his work in the committee for the defense of North Africa and the committee for the liberation of the Arab Maghrib. In addition to his interest in Islamic issues, particularly the Palestinian cause, which he fought for and kept fighting for, the Tunisian and Palestinian cause after he settled in Damascus until his death.
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي المعاصر
Keywords: محي الدين القليبي ،الحماية الفرنسية، الحركة الوطنية، الصحافة، الحزب الحر الدستوري، مؤتمر نهج الجبل، جماعة العمل التونسي ، اللجنة التنفيذية ، مؤتمر قصر الهلال، الحزب الدستوري القديم ، الحزب الدستوري الجديد،القضية الفلسطنية.; Mohieddine El-Qalibi, French protectorate, national movement, journalism, Constitutional Liberal Party, Nahj Al-Jabal conference, Tunisian Workers’ Party, Executive Committee, Qasr Al-Hilal conference, old Constitutional Party, new Constitutional Party, Palestinian cause